MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP MOTIVASI BELAJAR DAN PRESTASI BELAJAR IPA KELAS IV - Indradewi, Ni Nyoman Adi; Jampel, I Nyoman; Suastra, I Wayan (Jurnal Administrasi Pendidikan Indonesia, 2025)
The problem in this study departs from the low motivation and learning achievement of students in Natural Sciences (IPA) subjects at the elementary school level, which is caused by the use of conventional learning models that are still teacher-centered. This study aims to analyze the influence of the Problem Based Learning (PBL) model on the learning motivation and learning achievement of science students in grade IV of elementary school. The research subjects consisted of two groups, namely the experimental class that used the PBL model and the control class that used conventional learning methods. This study uses a quantitative approach with a quasi-experiment design in the form of a posttest-only control group design. The data collection technique is carried out through a learning motivation questionnaire and a science learning achievement test that has been validated by experts. Data were analyzed using descriptive and inferential statistical techniques, including analysis prerequisite tests (normality, homogeneity, and collinearity tests) and hypothesis testing with Variance Analysis (ANOVA) and Multivariate Analysis (MANOVA) using the help of SPSS 26.0 for Windows software. The results showed that there was a significant difference in learning motivation and science learning achievement between students who were taught with the Problem Based Learning model and students who were taught with the conventional learning model. The application of PBL has been proven to be able to increase student learning motivation through student-centered contextual learning, as well as improve science learning achievement through critical thinking processes, problem-solving, and group collaboration. Thus, the Problem Based Learning model can be recommended as an alternative to an effective learning strategy in improving the quality of science learning in elementary schools